"Slow" and "fast" in blue carbon: Differential turnover of allochthonous and autochthonous organic matter in minerogenic salt marsh sediments. Issue Volume 67:Issue S2(2022) (19th April 2022) - Komada, Tomoko; Bravo, Anthony; Brinkmann, Mandy‐Tanita; Lu, Kevin; Wong, Lily; Shields, Gavin
Abstract: Salt marshes are recognized as blue carbon ecosystems for their ability to rapidly sequester organic carbon (OC) via sedimentation. For this reason, there is growing interest in managing these systems to help mitigate climate change. However, in order for sediment accretion to offset ongoing CO2 emissions, organic matter undergoing burial must be derived from contemporary primary production. To investigate the provenance of OC sequestered by salt marshes, we analyzed the concentration and isotope composition (δ 13 C and Δ 14 C) of sedimentary OC in two minerogenic marshes in San Francisco Bay, California, USA. Data from the low marsh dominated by Spartina spp. show that autochthonous OC is entering the sediment matrix and may in part be stabilized through incorporation into the mineral‐bound pool. However, the sedimentary OC stock as a whole is dominated by material with low values of δ 13 C ( −20 to −25‰) and Δ 14 C ( 100 to −300‰) indicating a preponderance of allochthonous OC that was retained in other OC reservoirs for 10 2 to 10 3 years prior to deposition in the marsh. Diagenetic modeling of OC and its δ 13 C values further shows that autochthonous OC is lost from the sediment profile at a much faster rate than allochthonous OC. The rapid turnover of contemporary autochthonous OC ("fast carbon") relative to the apparent stability of old allochthonous OC ("slow carbon") suggest that carbon burial at these sites is largely decoupled from ongoing CO2 emissions.